Effect of Residual Water in Sediments on the CO2-CH4 Replacement Process - Fuqin Lu; Xuebing Zhou; Caili Huang; Dongliang Li; Deqing Liang (Energies, 2023)
CO2 replacement is a promising method of gas hydrate recovery. However, the influence of residual water in the replacement process and selections of a suitable mining area remain uncertain. To better understand this method, we examined the influence of the particle size and initial hydrate saturation on the replacement process while using the same amount of residual free water. The results showed that during the replacement process, two stages of rapid reaction and slow reaction occurred, which were manifested by the speed of pressure change in the reactor. The CO2 sequestration ratio decreased with the increase in sediment particle size and increased with the increase in initial hydrate saturation. During the replacement process, two reactions occurred: CH4 was replaced by CO2 and CO2 hydrate was formed, and the replacement amount and recovery efficiency of CH4 increased with a decrease in sediment particle size. When the sediment particle size was less than 166 μm, the CH4 recovery efficiency was significantly affected by the particle size. The replacement amount of CH4 increased with the increase in initial hydrate saturation, and the recovery efficiency decreased. This study provides a basis for selecting suitable hydrate-accumulation areas for on-site mining.